1998
DOI: 10.1074/jbc.273.43.28057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apoptosis-associated Proteins in a Human Burkitt Lymphoma Cell Line

Abstract: Apoptosis or programmed cell death is essential in the process of controlling lymphocyte growth and selection. We identified proteins that are involved in anti-IgM antibody-mediated apoptosis using a subclone of the human Burkitt lymphoma cell line BL60. Apoptosis-associated proteins were detected by high resolution twodimensional gel electrophoresis on a micropreparative scale. Comparison of the high resolution two-dimensional gel electrophoresis protein patterns from apoptotic and non-apoptotic cells showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
3
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 44 publications
10
114
3
3
Order By: Relevance
“…On the ground of the SRB assay results, IC 50 values of 0.5 and 0.3 lM were determined for auranofin on the sensitive and resistant cell lines, respectively, after 72-h drug exposure. In turn, the measured IC 50 values for Auoxo6 were found to be perfectly consistent with those previously reported by Casini et al [5] (1.8 and 4.9 lM for A2780/S and A2780/R, respectively). We also observed that very limited cell death was evident, for both compounds, at 24 h, this rendering a classic proteomic approach well feasible.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…On the ground of the SRB assay results, IC 50 values of 0.5 and 0.3 lM were determined for auranofin on the sensitive and resistant cell lines, respectively, after 72-h drug exposure. In turn, the measured IC 50 values for Auoxo6 were found to be perfectly consistent with those previously reported by Casini et al [5] (1.8 and 4.9 lM for A2780/S and A2780/R, respectively). We also observed that very limited cell death was evident, for both compounds, at 24 h, this rendering a classic proteomic approach well feasible.…”
Section: Resultssupporting
confidence: 91%
“…At the time point of the Auoxo6 and auranofin treatments studied, no increased apoptosis was observed. We observed that apoptosis occurs at a later time point and that the increase of heterogeneous nuclear ribonucleoprotein H levels just precedes this process [50].…”
Section: Functional Roles Of the Identified Proteinsmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the modified S19 serves as a chemoattractant specific for macrophages (12). Two more reports suggest the structural modification of ribosomes during apoptosis: cleavage or at least modification of the 60S ribosome subunit protein PO (15) and destruction of polysomes (1). These findings indicate that ribosomal proteins and the ribosome complex are structurally modified in apoptotic cells, and suggest that some ribosomal proteins have extra-ribosomal functions.…”
mentioning
confidence: 95%
“…Apoptosis studies on Burkitt lymphoma BL60 cells revealed various apoptosis-associated proteins not known in this process so far [117,118]. They gave clues about the apoptosis pathway, the caspases cascade and specific cleavage sites [119,120].…”
Section: Examples Of Successful Application Of Proteomicsmentioning
confidence: 99%